Memahami Konsep Reinhold Niebuhr tentang Keberagaman dan Kesatuan Sejarah - Hardiansyah Hardiansyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
Reinhold Niebuhr a Christian Protestant neo-orthodox wing yan, Niebuhr's view of man who was reported by the Bible higher than that. Niebuhr in addressing the diversity of prefer the attitude of pluralism. According to Niebuhr the development and fall of cultures and civilizations is caused by the absence of historical pluralism. The idea seems to lead to the formation of the unity of history. The core relationship of each civilization depict the unity of length in time. The essence of contemporary civilization relation to each other again describing the broad unity in the room, deeper unity is a real number.